Pharmacokinetics and Disposition of Rilpivirine (TMC278) Nanosuspension as a Long-Acting Injectable Antiretroviral Formulation - van ′t Klooster, Gerben (American Society for Microbiology (ASM), 2010)
The next-generation human immunodeficiency virus type 1 (HIV-1) nonnucleoside reverse transcriptase inhibitor rilpivirine (TMC278) was administered in rats and dogs as single intramuscular (IM) or subcutaneous (SC) injections, formulated as a 200-nm nanosuspension. The plasma pharmacokinetics, injection site concentrations, disposition to lymphoid tissues, and tolerability were evaluated in support of its potential use as a once-monthly antiretroviral agent in humans. Rilpivirine plasma concentration-time profiles showed sustained and dose-proportional release over 2 months in rats and over 6 months in dogs. The absolute bioavailability approached 100%, indicating a complete release from the depot, in spite of rilpivirine concentrations still being high at the injection site(s) 3 months after administration in dogs. For both species, IM administration was associated with higher initial peak plasma concentrations and a more rapid washout than SC administration, which resulted in a stable plasma-concentration profile over at least 6 weeks in dogs. The rilpivirine concentrations in the lymph nodes draining the IM injection site exceeded the plasma concentrations by over 100-fold 1 month after administration, while the concentrations in the lymphoid tissues decreased to 3- to 6-fold the plasma concentrations beyond 3 months. These observations suggest uptake of nanoparticles by macrophages, which generates secondary depots in these lymph nodes. Both SC and IM injections were generally well tolerated and safe, with observations of a transient inflammatory response at the injection site. The findings support clinical investigations of rilpivirine nanosuspension as a long-acting formulation to improve adherence during antiretroviral therapy and for preexposure prophylaxis.